Development of Game-based Learning to Improve Understanding of Energy Source Material for Deaf Students - Rizqita, Alya Jilan; Aprilia, Imas Diana; Sunardi, S; Hernawati, Tati; Maryanti, Rina; Bela, Muhammad Rafi Wirdan Assyakir Tandu (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This research aims to develop game-based learning to improve deaf students' understanding of energy source material. The research method used in this study is research and development (RnD) to obtain comprehensive information in analyzing the learning barriers experienced by deaf students as the basis for developing game-based learning media. The subjects in this study were deaf students in grade VII who experienced learning barriers in energy source material. The result of this research is game-based learning media on energy source material for deaf students in grade VII. The content and material of energy sources contained in the game-based learning media have been adjusted to the learning needs and characteristics of deaf students. The results showed that this game-based learning media is effective to improve the learning needs of deaf students on energy source material. In addition to being useful for deaf students, this educational game-based learning media is also expected to be used for other students who are learning science on energy source material.